Pengaruh Ukuran Perusahaan, Leverage, Risiko Sistematik, Dan Investment Opportunity Set Terhadap Earnings Response Coefficient Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2012-2014 - Ivan Kurnia; Sufiyati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The purpose of this research is to gain empirical evidence about the influence of firm size, leverage, systematic risk, and investment opportunity set on earnings response coefficient on manufacturing companies listed in Indonesia Stock Exchange for 2012-2014. Samples were selected by using the purposive sampling method. This research used a sample of one hundred forty-one manufacturing companies. The result of this research indicates that only systematic risk have an influence on earnings response coefficient while firm size, leverage, and investment opportunity set has not had an influence on earnings response coefficient. For better results, further research may add another variable that influences on earnings response coefficient.